2021
DOI: 10.3389/fnmol.2021.749716
|View full text |Cite
|
Sign up to set email alerts
|

Treating Metastatic Brain Cancers With Stem Cells

Abstract: Stem cell therapy may present an effective treatment for metastatic brain cancer and glioblastoma. Here we posit the critical role of a leaky blood-brain barrier (BBB) as a key element for the development of brain metastases, specifically melanoma. By reviewing the immunological and inflammatory responses associated with BBB damage secondary to tumoral activity, we identify the involvement of this pathological process in the growth and formation of metastatic brain cancers. Likewise, we evaluate the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 241 publications
0
8
0
Order By: Relevance
“…The NF‐κB signaling pathway is, however, also involved in maintaining cancer cell stemness. For example, NF‐κB maintains the stemness of colon cancer cells by down‐regulating miR‐195‐5p/497‐5p and up‐regulating MCM2 37 . To investigate whether NF‐κB is involved in mediating RIP2‐induced stemness of U251 cells, we observed the intervention effect of the NF‐κB chemical inhibitor SC75741.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The NF‐κB signaling pathway is, however, also involved in maintaining cancer cell stemness. For example, NF‐κB maintains the stemness of colon cancer cells by down‐regulating miR‐195‐5p/497‐5p and up‐regulating MCM2 37 . To investigate whether NF‐κB is involved in mediating RIP2‐induced stemness of U251 cells, we observed the intervention effect of the NF‐κB chemical inhibitor SC75741.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of many studies found that stem cell therapy may present an effective treatment for metastatic brain cancer and glioblastoma 37 . Therefore, eliminating glioma cell stemness is one of the critical strategies for clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells are also learned to possess resistance against chemo-and radiotherapies. 17,18 2 | FACTORS ASSOCIATED WITH BRAIN TUMOR AND BRAIN CSCS…”
mentioning
confidence: 99%